Inovasi Perancangan Virtual Animasi Kelas Pembelajaran Online KampusKita: IMERSIF - Danuputra, Bramanta Octa; Vicky Septian Rachman; Sabeth Uttara (KALBISCIENTIA Jurnal Sains dan Teknologi, 2024)
The role of online-based learning classes in all levels of education is a learning system that makes things that are prioritized in the Covid-19 which has hit since the early 2020. Indonesia in 2022 has entered a period of normalization, where the learning system in class online is still very much needed, but in this case the thing that is needed is an effective learning system innovation. In this case the immersive -based learning system program is an innovation solution that can provide the right solution in answering needs. Campuskita, is a visual campus in the world of metaverse, which can provide immersive online learning solutions that can be implemented to online class learning systems in all universities in Indonesia.